Mentoring for Digital Educational Game Development using Flash CS6 to Train Creative Thinking Skills of Students at SMA Negeri 10 Palembang - Leni Marlina; Ida Sriyanti; Sudirman; Imam Arif Pribadi; Melinda Maharani; Riska Anggraini; Gede Mudita Edi Putra; Windha; Zia Syawara; Muhammad Putra Aririyansyah (Pascasarjana Universitas Mataram, 2026)
This community service program aims to improve students’ creative thinking skills through mentoring in developing digital educational games using Adobe Flash CS6 at SMA Negeri 10 Palembang. The implementation was carried out through several stages, namely socialization, workshops, hands-on practice, and coaching clinic. A total of 24 students participated in both face-to-face and online sessions. Data were collected using pre-test, post-test, and a satisfaction questionnaire, and were analyzed quantitatively and qualitatively. The results showed a significant increase in students’ cognitive abilities, indicated by the improvement of the average score from 69.16 in the pre-test to 90.41 in the post-test. The N-Gain analysis demonstrated high improvement in the indicators of game concept (0.95) and design basics (1.00), while coding skills were in the moderate category (0.61). Students’ creative thinking skills also increased, particularly in fluency (83%), flexibility (74%), and originality (77%). In addition, the level of participant satisfaction reached 80–100% in all aspects assessed, indicating that the program was considered useful, easy to follow, and relevant to learning needs. Thus, mentoring in developing educational games with Adobe Flash CS6 is effective in enhancing digital literacy and creative thinking skills of high school students.